The Effects of Supporting Business Innovation and R and D Activities from European Union Funds in Poland: A Review of Evaluation Studies - Krupnik, Seweryn; Szczucka, Anna; Lisek, Katarzyna (Journal of Public Governance, 2022)
Objectives:In order to create more accurate public policies in the field of innovation subsidies, it is crucial to provide timely knowledge about the effectiveness of implemented interventions. This article explores the effects of EU programmes realised in Poland. The results are derived from evaluation reports. Research Design and Methods:The article is based on a review of the most important evaluation research concerning innovation policies implemented as a part of the operational programmes in Poland. Findings: The results from a review of evaluation studies show the impact of the policies on the innovativeness of Polish enterprises. An increase in indicators of innovation performance and R and D activities among the beneficiaries was observed. The achievements of particular enterprises translate into change at the macro level. However, there is not enough evidence to ascertain the sustainability of the programmes’ effects. Based on the gathered evidence, it is hard to indicate a straight link between an increase of innovation and higher competitiveness of beneficiaries. Implications: The results suggest a need for changes at different stages of the public policy cycle, namely design, implementation, and evaluation. Contribution / Value Added:The article gives a picture of today’s achievements in cohesive policy when it comes to innovation in enterprises; it sums up the knowledge about the effects of the implemented solutions, pointing out the fields that need more evidence.